Role and Function of Indonesian Child Protection Commission in Providing Against Victims of Violence in the Street - Fransiska Novita Eleanora; Andang Sari (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
The law of child protection is very important and determines the future of family, community, nation and state formation. If a country's child protection law is formulated, ratified, and enforced concretely in terms of substance, structure and culture applied consistently and continuously, then the position of the child both in family, community and nation will become a very strong pillar and foundation. for a country to achieve its objectives nationally independent. Improper treatment or discrimination is the duty and responsibility of guardians or other parties and their parents. Getting the right opportunity to protect and grow socially, physically, and even spiritually is absolutely given because the future leaders of the nation and the next generation will be able to fight for the nation and its ideals. Eliminating discrimination requires equality in all aspects of the field because it involves the same views and opportunities where women and men have equal access and opportunities, equality of views does not mean women must be equal to men, because women are naturally different from men. Because children are the generation and successors of the nation, the Government forms an independent institution whose task is to shade and provide protection or supervision of children who are victims of crime, namely the Indonesian Child Protection Commission (KPAI) providing data reporting and assisting these children to obtain rehabilitation or recovery related to their rights.